Analysis of Consumer Preferences in Digital Payment: Integration of TAM and TPB Model to Enhance Technology Adoption - Latifah, Eva; Daniel Tumpal Hamonangan Aruan (Jurnal Dinamika Manajemen, 2025)
This study investigates consumer preferences towards digital payments in Indonesia, employing the Technology Acceptance Model (TAM) and the Theory of Planned Behavior (TPB). Digital banking technologies, notably digital payments, offer several advantages, including convenience, flexibility, low costs, integrated features, and transaction efficiency. However, these technologies also encounter significant challenges, such as security risks, trust issues, and digital literacy gaps. To explore these dynamics, this research utilizes a conclusive design with a cross-sectional method and analyzes data through Structural Equation Modeling (SEM). The results confirm the majority of the proposed hypotheses, showing strong positive effects on factors like perceived usefulness, usability, resistance, risk perception, compatibility, and digital literacy. Notably, ease of interaction with the system is mainly shaped by user awareness. On the other hand, moderating factors such as communication, satisfaction, and trust have minimal impact and do not support the hypotheses. The results underscore that user perceived value, system simplicity, social influence, and personal attitudes play essential roles in driving technology acceptance. The study recommends that digital payment providers focus on enhancing user perceptions of functional value and intuitive design. Emphasizing clear advantages and fostering a supportive social environment can strengthen user adoption and long-term loyalty in the Indonesian market.